Beberapa Bentuk Hubungan Antara Franchisor (Pewaralaba) Dan Franchisee (Terwaralaba) Dalam Sistem Franchise (Waralaba) - Situmorang, James Rianto (Business Administration Study Program - Universitas Katolik Parahyangan, 2013)
Franchise is increasingly becoming an option for people who want to become anentrepreneur. Someone who has the capital to pay royalty fees and meet the re-quirements specified by the franchisor thus he/she soon became a franchisee. He/shecan immediately run the business without necessary start a business from zero. Infranchise business, franchisee operation can not be separated from control by thefranchisor as the owner of the franchise because the franchisee is bound to what iswritten on an agreement that has been made by the franchisor. In addition to theformal relationship between franchisee and franchisor, there is also a non formalrelationship between franchisee and franchisor. It can not be avoided because thefranchise system included in the model of agency theory and the franchisee to besuccessful so the closer relationship between the franchisee and the franchisor mustbe achieved in the form of trust.Keywords: Franchise, franchisor, franchisee, relationship, business